OP0051 STRUCTURAL ENTHESEAL LESIONS IN PSORIASIS PATIENTS ARE ASSOCIATED WITH AN INCREASED RISK OF PROGRESSION TO PSORIATIC ARTHRITIS - A PROSPECTIVE COHORT STUDY. (2nd June 2020) - Simon, D.; Tascilar, K.; Kleyer, A.; Bayat, S.; Kampylafka, E.; Hueber, A.; Rech, J.; Schuster, L.; Engel, K.; Sticherling, M.; Schett, G.
Abstract : Background: We have previously reported that the presence of musculoskeletal pain in psoriasis patients is associated with a higher risk of developing psoriatic arthritis (PsA) (1). Furthermore, a subset of psoriasis patients shows evidence for structural entheseal lesions (SEL) in their hand joints (2), sometimes also referred as "Deep Koebner Phenomenon", which are highly specific for psoriatic disease and virtually absent in healthy controls, rheumatoid arthritis and hand osteoarthritis patients (2-4). However, it remains unclear whether SEL alone or in combination with musculoskeletal pain are associated with the development of PsA. Objectives: To test whether the presence of SEL in psoriasis patients increases the risk for progression to PsA and how this is related to the presence of musculoskeletal pain. Methods: Psoriasis patients without evidence of PsA were enrolled in a prospective cohort study between 2011 and 2018. All patients underwent baseline assessment of SEL in their 2 nd and 3 rd MCP joints by high-resolution peripheral quantitative computed tomography (HR-pQCT). The risk of PsA development associated with SEL and arthralgia was explored using survival analyses and multivariable Cox regression models. Results: 114 psoriasis patients (72 men/42 women) with a mean (SD) follow-up duration of 28.2 (17.7) months were included, 24 of whom developed PsA (9.7 /100 patient-years, 95%CI 6.2 to 14.5) during the observation period. Patients with SEL (N=41) were at higher risk of developing PsA compared to patients without such lesions (21.4/100 patient-years, 95%CI 12.5 to 34.3, HR 5.10, 95%CI 1.53 to 16.99, p=0.008) (Kaplan Meier plot A). Furthermore, while patients without arthralgia and without SEL had a very low progression rate to PsA (1/29; 3.4%), patients with arthralgia but no SEL showed higher progression (5/33; 15.2%), which was in line with previous observations (1) (Kaplan Meier plot B). Presence of SEL further enhanced the risk for progression to PsA both in the absence (6/16; 37.5%) and presence (6/14; 42.8%) of arthralgia with the highest progression rate in those subjects with both arthralgia and SEL (p<0.001 by log rank test for trend) (Kaplan Meier plot B). Conclusion: Presence of SEL is associated with an increased risk of developing PsA in patients with psoriasis. If used together with pain, SEL allow defining subsets of psoriasis patients with very low and very high risk to develop PsA. References: [1]Faustini F et al. Ann Rheum Dis. 2016;75:2068-2074 [2]Simon D et al. Ann Rheum Dis. 2016;75:660-6 [3]Finzel S et al. Ann Rheum Dis. 2011;70:122-7 [4]Finzel S et al. Arthritis Rheum. 2011;63:1231-6 Disclosure of Interests: David Simon Grant/research support from: Else Kröner-Memorial Scholarship, Novartis, Consultant of: Novartis, Lilly, Koray Tascilar: None declared, Arnd Kleyer Consultant of: Lilly, Gilead, Novartis, Abbvie, Speakers bureau: Novartis, Lilly, Sara Bayat Speakers bureau: Novartis, Eleni Kampylafka Speakers bureau: Novartis, BMS, Janssen, Axel Hueber Grant/research support from: Novartis, Lilly, Pfizer, Consultant of: Abbvie, BMS, Celgene, Gilead, GSK, Lilly, Novartis, Speakers bureau: GSK, Lilly, Novartis, Jürgen Rech Consultant of: BMS, Celgene, Novartis, Roche, Chugai, Speakers bureau: AbbVie, Biogen, BMS, Celgene, MSD, Novartis, Roche, Chugai, Pfizer, Lilly, Louis Schuster: None declared, Klaus Engel: None declared, Michael Sticherling Grant/research support from: Novartis, Consultant of: Advisory boards Abbvie, Celgene, Janssen Cilag, Lilly, Pfizer, MSD, Novartis, Amgen, Leo, Sanofi, UCB, Speakers bureau: Abbvie, Celgene, Janssen Cilag, Leo, MSD, Novartis, Pfizer, Georg Schett Speakers bureau: AbbVie, BMS, Celgene, Janssen, Eli Lilly, Novartis, Roche and UCB